2022
DOI: 10.1038/s41467-022-30306-7
|View full text |Cite
|
Sign up to set email alerts
|

Reversing insufficient photothermal therapy-induced tumor relapse and metastasis by regulating cancer-associated fibroblasts

Abstract: Insufficient tumor accumulation and distribution of photosensitizers as well as low antitumor immunity severely restrict the therapeutic efficacy of photothermal therapy (PTT). Cancer-associated fibroblasts (CAFs) play a key role in tumor extracellular matrix (ECM) remodeling and immune evasion. Reshaping tumor microenvironment via CAF regulation might provide a potential approach for complete tumor elimination in combination with PTT. Here, tumor cell-derived microparticles co-delivering calcipotriol and Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 58 publications
0
74
0
Order By: Relevance
“…Specifically, VDR servers as a master genomic suppressor of pancreatic stellate cells (PSC) activation state and has the potential to revert PSCs into quiescent state. In this context, calcipotriol destroyed several tumor-supporting signaling pathways and enhanced the effects of chemotherapy in multiple mouse tumor models, which hindered the tumor-stroma interplay and tumor proliferation [439][440][441][442]. Some vitamin D analogues (e.g.…”
Section: Targeting Cafs For Cancer Therapymentioning
confidence: 99%
“…Specifically, VDR servers as a master genomic suppressor of pancreatic stellate cells (PSC) activation state and has the potential to revert PSCs into quiescent state. In this context, calcipotriol destroyed several tumor-supporting signaling pathways and enhanced the effects of chemotherapy in multiple mouse tumor models, which hindered the tumor-stroma interplay and tumor proliferation [439][440][441][442]. Some vitamin D analogues (e.g.…”
Section: Targeting Cafs For Cancer Therapymentioning
confidence: 99%
“…PTAs are injected into the body, and, using targeting technology, they accumulate near tumor tissue, where they damage the protein structure of tumor cells, resulting in a cure. PTT has the advantage of being able to use variable levels of external laser irradiation to precisely target the tumor while avoiding harm to the surrounding healthy tissue; it can also be used to treat all types of cancer and is non-invasive [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,16 In contrast, photothermal therapy (PTT) produces hyperthermia without oxygen consumption, and therefore, could efficiently ablate cancer cells and regulate TME under exogenous light irradiation. 17,18 It is also observed that hyperthermia diffusion from tumors and the unwanted accumulation of PTT agents in normal tissues could result in nonspecific damages to healthy cells. 19 To circumvent this problem, researchers innovated activatable PTT paradigms, such as tumoral acidic pH-activated PTT for cancer treatment, and demonstrated that these paradigms are quite effective in executing cancers while avoiding damage to normal tissues.…”
Section: Introductionmentioning
confidence: 99%